More children, more "efficacy": the relationship between fertility and self-efficacy among the post-80 s and post-90 s generations - Haibin Wei; Qiaoqi Wang; Yibo Wu; Peng Zhou (BMC, 2024)
Abstract Fertility punishment is a powerful interpretation of the low birth rate in contemporary China, but it is not consistent with the fact that the proportion of second children has been increasing year by year for some time. From the perspective of Bandura's "Self-efficacy", based on the post-80 s and post-90 s youth samples in the Psychology and Behavior Investigation of Chinese Residents 2021, this paper explores the quantitative relationship between the number of children and individual self-efficacy. The data indicates that: (1) Fertility is closely linked to self-efficacy, with young people who have two children exhibiting higher self-efficacy; (2) The quantitative relationship between the number of children and self-efficacy varies based on parental roles-men/fathers show almost no change in self-efficacy when moving from having no children to one child, but demonstrate a significant increase in self-efficacy when they have two children. In contrast, women/mothers experience the lowest self-efficacy when having one child, which only shows a significant improvement when they have two children. These findings provide a new perspective for theoretically explaining the current fertility situation and expand the application of self-efficacy. In terms of policy efforts, it is necessary to provide support for women's one-child fertility, and to increase the publicity of the view of more children and more efficacy to resist the potential energy of low fertility that arises from the view of more children and more burdens.